Self-efficacy and its relationship to learning motivation among fourth-grade students in the city of Hama: الكفاءة الذاتية وعلاقتها بدافعية التعلم لدى تلاميذ الصف الرابع الأساسي (Journal of Hama University, 2024)
The study aimed to identify the relationship between self-efficacy and learning motivation among fourth-grade students. To achieve this, a measure of self-efficacy and a measure of learning motivation were used, ensuring their validity and reliability, and then applying them to (229) male and female students in the fourth grade. The study showed the following results. :- There is a strong positive relationship between self-efficacy and learning motivation among fourth grade students. - Fourth grade students have moderate self-efficacy and learning motivation.-There are statistically significant differences between the averages of students’ answers on the self-efficacy scales due to the gender variable. -There are no statistically significant differences between the averages of students’ answers on the self-efficacy and learning motivation scales due to the gender variable. The research presented a set of recommendations, the most important of which are: working to develop self-efficacy and learning motivation among learners in general and students in the first cycle of basic education in particular, through carrying out appropriate activities and using appropriate teaching methods that help in this, and providing a supportive and encouraging educational environment for students. It enhances their self-efficacy and develops their motivation to learn.
Keywords: self-efficacy - learning motivation - fourth grade students.